Pawing the way to self-empoverment through a right-based education - Spajić-Vrkaš, Vedrana (Array, 2012)
The paper points out at the complexity of demands facing teachers and schools in a post-communist and a post-war Croatian context, in which education was seen as a tool for building Croatia as both the nation-state and the democratic society. In order to respond to these demands, a group of university professors, educational researchers and civil activists developed an integrative rights-based approach to education heavily informed by the human rights education principles. The approach fosters human rights learning through five dimensions: self-awareness and identity ; respect for diversity ; being a democratic citizen ; peaceful conflict-resolution and global perspective. This approach became the basis for the development of the National Human Rights Education Programme for all school levels, including the university, the resource materials, including the manual and the dictionary.